2022
DOI: 10.1021/acs.jpclett.2c01100
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Photocatalytic Active Sites of C2H6 C–H Bond Activation on TiO2 via Combining First-Principles Ground-State and Excited-State Electronic Structure Calculations

Abstract: The activation of C–H bonds at low temperatures has attracted widespread interest in heterogeneous catalysis, which involves complex thermocatalytic and photocatalytic reaction processes. Herein, we systematically investigate the photothermal catalytic process of C–H bond activation in C2H6 dehydrogenation on rutile TiO2(110). We demonstrate that the photochemical activity of the C2H6 molecule adsorbed on TiO2(110) is site-sensitive and that C2H6 is more easily adsorbed at the Ti5c site with a lower dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…However, when the O b 2− and O Ti 2− centers trap photogenerated holes, the nucleophilic O b 2− and O Ti 2− convert into electrophilic O b − and O Ti − centers, 47,48 which have a stronger ability than O b 2− and O Ti 2− to abstract the H atoms of the small alkanes. 20,21,25 Correspondingly, the study of the photocatalytic EB dehydrogenation on R-TiO 2 (110) 39 demonstrated that both the O b − and O Ti − centers produced by trapping the holes can activate the α-C–H bond of the side chain alkyl groups of EB. In addition, theoretical works also suggest that the O b − centers formed upon the UV irradiation play a vital role in the C–H bond activation of CH 4 and C 2 H 6 on R-TiO 2 (110).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the O b 2− and O Ti 2− centers trap photogenerated holes, the nucleophilic O b 2− and O Ti 2− convert into electrophilic O b − and O Ti − centers, 47,48 which have a stronger ability than O b 2− and O Ti 2− to abstract the H atoms of the small alkanes. 20,21,25 Correspondingly, the study of the photocatalytic EB dehydrogenation on R-TiO 2 (110) 39 demonstrated that both the O b − and O Ti − centers produced by trapping the holes can activate the α-C–H bond of the side chain alkyl groups of EB. In addition, theoretical works also suggest that the O b − centers formed upon the UV irradiation play a vital role in the C–H bond activation of CH 4 and C 2 H 6 on R-TiO 2 (110).…”
Section: Resultsmentioning
confidence: 99%
“…Namely, the initial C–H bond activation of C 2 H 6 on R-TiO 2 (110) seems to occur ineffectively at the ground state via thermocatalysis. 21,22,24…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the desorption temperature of HT C 6 H 5 CHCH 2 , the energy barrier of the second C–H bond cleavage on the ground state is about 1–1.3 eV. The energies of photogenerated electrons/holes by 257 nm (∼4.8 eV) and 343 nm (∼3.6 eV) light are much higher than the energy barrier, while a series of theoretical works on photocatalytic C–H bond activation on R–TiO 2 (110) ,, suggest that the formation of an excited radical intermediate by trapping a hole will largely decrease the energy barrier of the C–H bond cleavage and then facilitate the C–H bond cleavage. In addition, when one methyl group on the end of the C 3 H 8 molecule is substituted by a phenyl group, C 6 H 5 C 2 H 5 forms.…”
mentioning
confidence: 99%
“…Many terminal metal-oxo complexes serve as active sites for activating the strong C–H bonds of light alkanes at moderate reaction conditions. However, the fleeting nature of these metal-oxo intermediates makes it difficult to probe them experimentally. Density functional theory (DFT) has been extensively used to computationally model metal-oxo intermediates to understand their role in C–H bond activation. Furthermore, computational modeling using DFT can help in finding out structure–activity relationships that will speed the discovery of efficient catalysts and hence guide experimental efforts toward their synthesis. …”
mentioning
confidence: 99%